Autorzy:Joanna Czarnowska, Jolanta Wesołowska, Wojciech Babiański, Lech Chańko
Wydawnictwo:Nowa Era
Rok wydania:2014
Rozwiąż równanie 5.0 gwiazdek na podstawie 7 opinii

`a)` 

`(x-1)^2=(x+1)(x-1)` 

`x^2-2*x*1+1^2=x^2-1^2` 

`x^2-2x+1=x^2-1\ \ \ \ |-x^2` 

`-2x+1=-1\ \ \ |-1` 

`-2x=-2\ \ \ |:(-2)` 

`x=1` 

 

 

 

`b)` 

`(2x+1)^2=4(x+2)(x-2)` 

`(2x)^2+2*2x*1+1^2=4(x^2-2^2)` 

`4x^2+4x+1=4x^2-16\ \ \ |-4x^2` 

`4x+1=-16\ \ \ |-1` 

`4x=-17\ \ \ |:4` 

`x=-17/4` 

 

 

 

`c)` 

`9(1-2x)^2-4(3x-1)^2=1` 

`(3(1-2x))^2-(2(3x-1))^2=1` 

`[3(1-2x)-2(3x-1)]*[3(1-2x)+2(3x-1)]=1` 

`[3-6x-6x+2]*[3-6x+6x-2]=1` 

`(5-12x)*1=1` 

`5-12x=1\ \ \ |-5` 

`-12x=-4\ \ \ |:(-12)` 

`x=4/12=1/3` 

 

 

`d)` 

`(3x-2)(3x+2)=9(x-1/3)^2` 

`(3x)^2-2^2=9(x^2-2*x*1/3+(1/3)^2)` 

`9x^2-4=9(x^2-2/3x+1/9)` 

`9x^2-4=9x^2-6x+1\ \ \ |-9x^2` 

`-4=-6x+1\ \ \ |+6x` 

`6x-4=1\ \ \ |+4` 

`6x=5\ \ \ |:6` 

`x=5/6`